Covid-19 in kidney transplant recipients: a systematic review of the case series available three months into the pandemic. Issue 11 (1st November 2020) - Oltean, Mihai; Søfteland, John Mackay; Bagge, Jasmine; Ekelund, Jan; Felldin, Marie; Schult, Andreas; Magnusson, Jesper; Friman, Vanda; Karason, Kristjan
Abstract: Background: Coronavirus disease 2019 (COVID-19) ranges from a mild illness to acute respiratory distress syndrome (ARDS), multiorgan dysfunction, and death. Transplant recipients are vulnerable due to comorbidities and immunosuppressants that render them susceptible to infections. The information on COVID-19 in kidney transplant recipients remains limited to small case series. Methods: A systematic literature search was conducted, and 12 case series totalling 204 kidney transplant recipients with COVID-19 were identified. Data were extracted, pooled and analysed. Results: Most patients (74%) were men. The most frequent symptoms were fever (76%), cough (64%) and dyspnoea (43%). At admission, over 70% of the patients had abnormal radiological findings. Leukocyte counts were in the lower normal range. C-reactive protein, ferritin, and D-dimer were consistently increased. Treatments included lowering immunosuppression, hydroxychloroquine, antivirals, tocilizumab and intravenous immunoglobulins. Thirty-one percent of the patients were admitted to intensive care units (ICUs), and 16% required intubation. The overall mortality was 21.2%. Patients who died were significantly older than those who survived (61 ± 12 vs. 51 ± 15, p < .01). Logistic regression revealed that the odds for death increased by 4.3% for each additional year of age (odds ratio [OR] 1.043, 95% confidence interval [CI] 1.005–1.083, p value = .0265). Conclusions: No substantial conclusions could be drawn on the efficacy of any particular treatment. More rigorous patient stratification is needed when analysing and reporting data to facilitate future meta-analyses.